EDA-fibronectin originating from osteoblasts inhibits the immune response against cancer - Rossnagl, Stephanie; Altrock, Eva; Sens-Albert, Carla; Kraft, Sabrina; Huck, Katrin; Milsom, Michael; Giese, Thomas; Samstag, Yvonne; Nakchbandi, Inaam (PLoS biology, 2016)
Osteoblasts lining the inner surface of bone support hematopoietic stem cell differentiation by virtue of proximity to the bone marrow. The osteoblasts also modify their own differentiation by producing various isoforms of fibronectin (FN). Despite evidence for immune regulation by osteoblasts, there is limited knowledge of how osteoblasts modulate cells of the immune system. Here, we show that extra domain A (EDA)-FN produced by osteoblasts increases arginase production in myeloid-derived cells, and we identify α5β1 as the mediating receptor. In different mouse models of cancer, osteoblasts or EDA-FN was found to up-regulate arginase-1 expression in myeloid-derived cells, resulting in increased cancer growth. This harmful effect can be reduced by interfering with the integrin α5β1 receptor or inhibiting arginase. Conversely, in tissue injury, the expression of arginase-1 is normally beneficial as it dampens the immune response to allow wound healing. We show that EDA-FN protects against excessive fibrotic tissue formation in a liver fibrosis model. Our results establish an immune regulatory function for EDA-FN originating from the osteoblasts and identify new avenues for enhancing the immune reaction against cancer.